Servicios del Programa Nacional de Asistencia Solidaria Pensión 65 y condiciones de vida de adultos mayores, Distrito de Lucma, 2022 - Vasquez Soto, Deysi Elvira (2022)
This thesis entitled Services of the National Solidarity Assistance Program Pension 65 and living conditions of older adults, District of Lucma, 2022, aims to analyze the influence of the services provided by this program on the living conditions of older adults. For this, a sample of 159 beneficiaries was taken, most of whom are female, whose ages range from 70 to 95 years. The methods used in this research were inductive - deductive, analytical - synthetic and statistical; the techniques used were the survey, observation interview; which have made it possible to collect information about the perception that older adults have regarding the services provided by the Pension 65 program. Likewise, their respective instruments were used, including the survey questionnaire, guide and interview record, guide and observation record thus obtaining data on the variables and indicator to be measured in the investigation. The results obtained show that the services provided by the Pension 65 National Solidarity Assistance Program have a direct influence on the living conditions of the elderly, and that is that with the economic subsidy they receive on a bimonthly basis, it allows them to have an increase in their economic income and have free access to health through the SIS. Therefore, it is determined that they have physical well-being and material wellbeing, having access to basic services, which allows them to have a dignified and healthy life.